1995
DOI: 10.1093/carcin/16.10.2575
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation by butylated hydroxytoluene of the number and function of gap junctions in epithelial cell lines derived from mouse lung and rat liver

Abstract: The mouse pneumotoxicant and lung and liver tumor promoter butylated hydroxytoluene (BHT) was examined for its effects on gap junctional intercellular communication (GJIC) in mouse lung epithelial (C10) and rat liver epithelial (WB-F344) cell lines. GJIC, as measured by fluorescent dye microinjection, was inhibited in both types of cells by BHT in dose- and time-dependent fashions. Inhibition was detected in WB-F344 cells at BHT concentrations > or = 62.5 microM and in C10 cells at concentrations > or = 150 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 0 publications
1
19
0
1
Order By: Relevance
“…Second, the ability of TS to inhibit GJIC suggests that, at least in some conditions, it behaves like a tumor promoter [24,25]. Our results support epidemiological data suggesting the absence of a protective effect of vitamin E against cancer and even more its potential adverse effect: for example, a pooled analysis of prospective studies reported no protective effect of dietary vitamin E on lung cancer [48].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Second, the ability of TS to inhibit GJIC suggests that, at least in some conditions, it behaves like a tumor promoter [24,25]. Our results support epidemiological data suggesting the absence of a protective effect of vitamin E against cancer and even more its potential adverse effect: for example, a pooled analysis of prospective studies reported no protective effect of dietary vitamin E on lung cancer [48].…”
Section: Discussionsupporting
confidence: 81%
“…GJIC can be modulated by endogenous and exogenous agents. Most tumor promoters inhibit GJIC [24,25]; conversely, molecules having antipromoter activities can enhance GJIC [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Reduction of gap junction communication often occurs at the promotion/progression stages of carcinogenesis. Many tumor promoters can disrupt gap junction communication (GJC) such as 12-O-tetradecanoylphorbol-13-acetate (TPA) [18,19], H 2 O 2 [20,21], okadaic acid [22] (our unpublished data) and butylated hydroxytoluene [23]. These data suggest that reduced expression of cx43 is related to tumor development rather than initiation of tumorigenesis.…”
Section: Discussionmentioning
confidence: 83%
“…(Witschi and Morse 1985). Recently, BHT has been reported also to induce inhibition of gap junctional intercellular communication and apoptosis in lung epithelial cells (Dwyer-Nield et al 1998;Guan et al 1995). Although any link between these events and the mechanisms underlying the tumorpromoting activity of BHT remains uncertain, it is likely that metabolites of BHT resulting from hydroxylation of a tert-butyl group by P450 isozymes play a key role in the chain of events leading to lung tumor development (Thompson et al 1989).…”
Section: Discussionmentioning
confidence: 99%